Divergence and Convergence of Firm-Level Best Practices: The Case of Bajaj and Hero-Honda in India's Two-Wheeler Industry. Issue 4 (1st October 2016) - Patibandla, Murali
ABSTRACT: This article examines micro-level issues of competitive rivalry of firms and the consequent convergence of best practices. Multinational investment in developing economies is one of the means of technology inflows. If local firms have a critical level of capabilities and are able to compete with multinational firms, this can lead to convergence of best practices. This, in turn, helps local firms in a developing economy to acquire capabilities for internationalization. The issue of convergence is examined with the case of rivalry between a large local firm (Bajaj) and a giant multinational corporation (Hero-Honda) in India's two-wheeler industry.